The Reinvention of Religious Music : Olivier Messiaen's Breakthrough Toward the Beyond - Maas, Sander van, 1968- (Book collections on Project MUSE., 2009)
Present-day music studies conspicuously evade the question of religion in contemporary music. Although many composers address the issue in their work, as yet there have been few attempts to think through the structure of religious music as we hear it. On the basis of a careful analysis of Olivier Messiaen's work, this book argues for a renewal of our thinking about religious music. Addressing his notion of a "hyper-religious" music of sounds and colors, it aims to show that Messiaen has broken new ground. His reinvention of religious music makes us again aware of the fact that religi.